Descompassos nas políticas educacionais: a reorganização da educação rural em Jardim de Piranhas/RN - Azevedo, Márcio Adriano de (2006)
The present work has as aim to analyze the reorganization process of the rural education in Jardim de Piranhas-RN, on the context of the education policies, in particular of the period of 1999-2006, having as reference the transformations in the political, cultural and socio-economic setting in the national, regional and local level, above all from the decade of 1990. The studies carried out in diverse sources made possible to understand from the context in which they had developed the education policies, in particular, that one directed for the rural way, as well as the mediation of this with the education reorganization in the local scope. Besides these research procedures, we carry out interviews - semi-structuralized - with managers and teachers, and we analyze documents from the produced ones in national level to those local ones. From the viewpoint theoretician-methodological, we focus the national discussion that comes developing under a new ideological political configuration and, being entitled by the Field Education, understood as a policy directed to education specifities in this sector and consolidated in the Operational Guidelines for the Basic Education in the Field Schools (CNE/MEC/2002). As particularity of this object in Jardim de Piranhas-RN, we emphasize events occurred that had marked the rural education reorganization in that city, especially from the creation of the Rural Education named Center Teacher Maria Edite Batista. Studies make possible to realize that until the Center creation, the schools functioned in rather precarious infrastructure and physical conditions, that is, without electric energy and water supplying, as well as the lack of school snack and the management structure. There was not a project or specific pedagogical accompaniment for the sector. Moreover, the teachers worked predominantly with several grade classes and still they fulfilled the manager functions, caretakers, and cook- in some cases as school secretary. However, exactly with the creation of the Rural Education Center, the education municipal system did not become capable to overcome problems as of the evasion and school failure, as well as decreasing the work overload of teachers, neither to give greater consistency to the pedagogical project of the field schools in that city